No quick end to the coronavirus shock in Germany - Hubertus Bardt; Michael Grömling (Institut der deutschen Wirtschaft (IW), 2020)
The coronavirus pandemic is likely to result in Germany's largest economic downturn in the last seven decades. Clarity as to the extent and course of the current adverse effects on business activity is being sought based on the regular business survey by the German Economic Institute (IW). Since there has so far been no fundamental differentiation between businesses' short and medium-term outlook, the coronavirus crisis is set to cast a long shadow over the German economy.
Keywords: 330